TREE SPECIES DIVERSITY AND DISTRIBUTION PATTERNS OF PROTECTED AREAS OF SAVANNA ECOSYSTEM OF NORTHERN NIGERIA - Iyagin, Faithful Olayinka; Adekunle, Victor; Lawal, Amadu; Alfa, Jerry Idoko (FUDMA JOURNAL OF SCIENCES, 2026)
Savanna ecosystems are shaped by complex interactions among disturbances, climate extremes, and management, yet quantitative assessments of their structural and floristic characteristics in Nigeria remain limited. This study, therefore, examined the present status of protected areas (PAs) within the savanna ecological zone of Northern Nigeria, focusing on tree species diversity, abundance, stand structure, density, and distribution patterns with the view of providing information for management and conservation purposes. Data were collected from five randomly selected PAs: Yankari Game Reserve and Sumu Wildlife Park (Bauchi State), Kainji Lake National Park and Borgu Game Reserve (Niger State), and Marhai Forest Reserve (Nasarawa State). A systematic line-transect sampling technique was used, with four 50 m × 50 m plots established at 250 m intervals in alternate directions within each site. All trees with DBH ≥10 cm were measured and identified. A total of 1,051 trees, 71 species and 22 families were recorded. Tree density ranged from 68 to 275 trees ha⁻¹. Combretaceae and Fabaceae were the most dominant families, while Combretum micranthum, Anogeissus leiocarpa, and Vitellaria paradoxa were the most frequent species. Despite low population density, Adansonia digitata contributed substantially to basal area and volume. Kainji recorded the highest Shannon index (3.21), evenness (0.95) and Margalef’s index of species richness (6.87). Tree density and height varied significantly (p<0.05), but basal area and DBH did not differ. Strong correlations between structural variables and diversity indices highlight the need to conserve and protect large-tree growth in the Nigerian savanna.